Discovery of natural anthraquinones as potent inhibitors against pancreatic lipase: structure-activity relationships and inhibitory mechanism - Zi-Qiang Chen; Wen-Yao He; Si-Yuan Yang; Hong-Hong Ma; Jing Zhou; Hao Li; Ya-Di Zhu; Xing-Kai Qian; Li-Wei Zou (Taylor & Francis Group, 2024)
Obesity is acknowledged as a significant risk factor for various metabolic diseases, and the inhibition of human pancreatic lipase (hPL) can impede lipid digestion and absorption, thereby offering potential benefits for obesity treatment. Anthraquinones is a kind of natural and synthetic compounds with wide application. In this study, the inhibitory effects of 31 anthraquinones on hPL were evaluated. The data shows that AQ7, AQ26, and AQ27 demonstrated significant inhibitory activity against hPL, and exhibited selectivity towards other known serine hydrolases. Then the structure-activity relationship between anthraquinones and hPL was further analysed. AQ7 was found to be a mixed inhibition of hPL through inhibition kinetics, while AQ26 and AQ27 were effective non-competitive inhibition of hPL. Molecular docking data revealed that AQ7, AQ26, and AQ27 all could associate with the site of hPL. Developing hPL inhibitors for obesity prevention and treatment could be simplified with this novel and promising lead compound.